Salvage Trans‐Sylvian Peri‐Insular Hemispherotomy After Embolic Hemispherectomy - Michael E. Baumgartner; Sudha Kessler; Kathleen Galligan; James E. Baumgartner; Benjamin C. Kennedy (Annals of the Child Neurology Society)
ABSTRACT Background Hemispherectomy and hemispherotomy represent well‐established treatments for drug‐resistant hemispheric epilepsy. An alternative endovascular procedure has been explored for cases with challenging surgical anatomy, which seeks to achieve the clinical effect of hemispherectomy via embolization of the major cerebral arteries and subsequent hemispheric infarction. Neither the safety nor effectiveness of this procedure has been established. Patient Description A 4‐month‐old girl with a history of drug‐resistant focal epilepsy due to left‐sided hemimegalecephaly previously treated with endovascular hemispherectomy at another institution presented for surgical evaluation due to ongoing electroclinical seizures despite multiple antiseizure medications. Pre‐operative magnetic resonance imaging (MRI) revealed viable tissue, including mesial temporal structures, and a salvage hemispherotomy was performed. The embolized cortex was surprisingly well‐perfused intra‐operatively. Postoperatively, she has had no further seizures at 1‐year follow‐up. Conclusion Embolization of the three large hemispheric arteries achieved neither complete hemispheric destruction nor complete disconnection in this case and did not resolve the patient's seizures, necessitating salvage hemispherotomy. While it is difficult to draw definitive conclusions from a single patient's course, our experience suggests that endovascular hemispheric destruction may not be an effective substitute for surgical hemispherectomy or hemispherotomy.